Opinions of Instructors on The Teaching Methods of Turkish Music in Cello Education - Burcu Avcı Akbel (Anı Publishing, 2018)
This research is a qualitative study aiming to reveal teaching methods for Turkish Music in cello education at music teacher training departments of universities in Turkey and to assess the process from the perspectives of academicians working at such departments. This is a descriptive study in which literature review and interview methods were used. The interview form, developed as a data collection tool in the study, was given its final form in line with expert opinions. As a result of content analysis performed in this study, it was revealed that Turkish Music education is taught only if the teacher has an interest in the field or if they deem it necessary; that the course content only includes adaptations or arrangements transcribed into tempered system, and that usul structures were the most challenging subject for students in Turkish Music performance. The reasons for not including Turkish Music in curricula of cello education at teacher training institutions were seen to include lack of resources, qualification of the trainers, not familiar with Turkish Music, methodology, the opinion that tonal and microtonal music education cannot be both included in the same curriculum, students' lack of theoretical background to learn Turkish Music